Engineered and decellularized human cartilage graft exhibits intrinsic immunosuppressive properties and full skeletal repair capacity - Alejandro Garcia Garcia; Sujeethkumar Prithiviraj; Deepak Bushan Raina; Tobias Schmidt; Sara Gonzalez Anton; Laura Rabanal Cajal; David Hidalgo Gil; Magnus Tägil; Axel Hyrenius-Wittsten; Madelene W. Dahlgren; Robin Kahn; Paul E. Bourgine (Proceedings of the National Academy of Sciences, 2026)
Tissue engineering strategies predominantly consist of the autologous generation of living substitutes capable of restoring damaged body parts. Persisting challenges with patient-specific approaches include inconsistent performance, high costs, and delayed graft availability. Toward developing a one-for-all solution, a more attractive paradigm lies in the exploitation of dedicated cell lines for the fabrication of human tissue grafts. Following decellularization, this new class of biomaterials relies on the sole extracellular matrix and embedded growth factors instructing endogenous repair. This conceptual approach was previously validated using a custom mesenchymal cell line for the manufacturing of human cartilage, exhibiting remarkable osteoinductive capacity following lyophilization. Key missing criteria to envision clinical translation include proper decellularization as well as stringent assessment of both immunogenicity and regenerative performance. Here, we report the engineering and subsequent decellularization of human cartilage tissue with minimal matrix impairment. Ectopic evaluation in immunocompetent (IC) and immunocompromised animals reveals preservation of osteoinductivity predicted by macrophage kinetic of polarization. By establishing in vitro human allogeneic coculture models, we evidenced the immunosuppressive properties of cell-free human cartilages, controlling macrophage and dendritic cell maturation as well as T cell activation. Finally, regenerative performance was stringently assessed in an IC rat orthotopic model whereby decellularized human cartilage grafts achieved morphological and mechanical restoration of all critical-sized femoral defects. Taken together, our study provides robust safety and efficacy prerequisites prompting a first-in-human trial for engineered and decellularized human tissue grafts.